Igor [videorecording (DVD)] - Doyle, Patrick; Schneid, Herve; Besson, Olivier; Eraklis, John D; Howard, Max; McKenna, Chris; Leondis, Tony; Cusack, John, 1966-; Buscemi, Steve, 1957-; Cleese, John; Coolidge, Jennifer; Hall, Arsenio; et al. (20th Century Fox Home Entertainment, 2008)
In a world filled with mad scientists and evil inventions, one talented evil scientist's hunch-backed lab assistant has big dreams of becoming a mad scientist himself. He dreams of winning the annual evil science fair. Determined to prove he can create his own diabolical invention, Igor creates a female Franken-monster. But his creation, Eva, is sweet and sings. That is, until she falls into the clutches of Dr. Schadenfreude.